2006
DOI: 10.1104/pp.105.075150
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into the Molecular Basis of Salt Tolerance of l-myo-Inositol 1-P Synthase (PcINO1) from Porteresia coarctata (Roxb.) Tateoka, a Halophytic Wild Rice

Abstract: The molecular basis of salt tolerance of L-myo-inositol 1-P synthase (MIPS; EC 5.5.1.4) from Porteresia coarctata (Roxb.) Tateoka (PcINO1, AF412340) earlier reported from this laboratory, has been analyzed by in vitro mutant and hybrid generation and subsequent biochemical and biophysical studies of the recombinant proteins. A 37-amino acid stretch between Trp-174 and Ser-210 has been confirmed as the salt-tolerance determinant domain in PcINO1 both by loss or gain of salt tolerance by either deletion or by ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 64 publications
0
52
0
Order By: Relevance
“…There is overwhelming evidence that stress genes from adapted species are eVective in the perception of stress signal and eventually trigger down stream structurally and functionally eYcient proteins, shown to be involved in protecting cellular structures and molecules under stress (Waditee et al 2002;Majee et al 2004;Dastidar et al 2006). Our physiological studies revealed that peanut is a relatively drought tolerant crop in comparison to sunXower, beans and tomato.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…There is overwhelming evidence that stress genes from adapted species are eVective in the perception of stress signal and eventually trigger down stream structurally and functionally eYcient proteins, shown to be involved in protecting cellular structures and molecules under stress (Waditee et al 2002;Majee et al 2004;Dastidar et al 2006). Our physiological studies revealed that peanut is a relatively drought tolerant crop in comparison to sunXower, beans and tomato.…”
Section: Discussionmentioning
confidence: 81%
“…Realizing this, it would be more rewarding to explore crop species with higher levels of stress tolerance at molecular level. Evidences support the fact that stress responsive genes from tolerant species provide better protection to cellular structures due to existence of genes that code for structurally and/or functionally eYcient stress proteins associated with stress adaptation (Waditee et al 2002;Majee et al 2004;Dastidar et al 2006). There is tremendous amount of biological diversity among diVerent plant species that necessitates sampling of other plant genome sequences, to understand the diversity of gene content and basic functional resolution of the plant genomes in general.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many MIPS genes have been identified in various prokaryotic and eukaryotic cells. In plants, characterization of MIPSs from diverse plant species revealed their important roles in stress responses (Nelson et al, 1998;Ghosh Dastidar et al, 2006;Murphy et al, 2008) and in the regulation of phytate, the fully phosphorylated form of myo-inositol and the major phosphorus storage compound in seeds (Hegeman et al, 2001;BrinchPedersen et al, 2002;Stevenson-Paulik et al, 2005). There are three MIPS genes in Arabidopsis; the MIPS1 gene was the first to be functionally identified by complementation of the yeast ino1 mutant and to date is the best-characterized MIPS gene (Johnson and Sussex, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…), and organic and amino acids like malate and proline, and many redoxregulating compounds such as glutathione, cystein and ascorbate and synthesis of LEA group of proteins have been documented in various plant species [20][21]. Metabolically engineered transgenics, leading for increase synthesis and accumulation of osmolytes of various natures have been shown to protect the plant against salinity stress [22][23][24]. It is presumed that while maintaining the cell turgor pressure in salt-stressed plants, the osmolytes also behave as osmo-protectants towards membrane-protein complexes and enzyme-proteins, and protect them from salt-induced impairments [25].…”
Section: Introductionmentioning
confidence: 99%